XMM–Newton observations of the extremely X-ray luminous quasar CFHQS J142952+544717=SRGE J142952.1 + 544716 at redshift z = 6.18. Issue 1 (26th March 2021) - Medvedev, P; Gilfanov, M; Sazonov, S; Schartel, N; Sunyaev, R
ABSTRACT: We present results from a 20 ks XMM–Newton director's discretionary time observation of the radio-loud quasar CFHQS J142952 + 544717 at z = 6.18, whose extreme X-ray luminosity was recently revealed by the SRG / eROSITA telescope in the course of its first all-sky survey. The quasar has been confidently detected with a total of ∼1400 net counts in the 0.2–10 keV energy band (1.4–72 keV in the object's rest frame). Its measured spectrum is unusually soft and can be described by an absorbed power-law model with a photon index of Γ = 2.5 ± 0.2. There are no signs of a high-energy cut-off or reflected component, with a 90 per cent upper limit on the fluorescence iron K α equivalent width of ≈290 eV and the corresponding upper limit on the iron K-edge absorption depth of 0.6. We have detected, at the >95 per cent confidence level, an excess absorption above the Galactic value, corresponding to a column density N H = 3 ± 2 × 10 22 cm −2 of material located at z = 6.18. The intrinsic luminosity of CFHQS J142952 + 544717 in the 1.4–72 keV energy band is found to be $5.5_{-0.6}^{+0.8} × 10^{46}$ erg s −1 . We did not detect statistically significant flux changes between two SRG scans and the XMM–Newton observation, spanning over ∼7.5 months, implying that the quasar remained at this extremely high-luminosity level for at least a month in its rest frame. We put forward the hypothesis that the extreme X-ray properties of CFHQS J142952 + 544717 are associated with inverse Compton scattering of cosmic microwave background photons (at z = 6.18) in its relativistic jets.